IMPLEMENTASI KONSELING INKLUSIF BAGI ANAK TUNARUNGU DALAM MENGEMBANGKAN REGULASI EMOSI DAN PENYESUAIAN SOSIAL - Heny Kristiana Rahmawati; Muhammad Ridwan; Nada Aliza Khoirunnisa (LPPM IAD Probolinggo, 2026)
Deaf children experience limitations in verbal communication that significantly affect their emotional regulation and social adjustment. These conditions require inclusive and adaptive guidance and counseling services. This study aims to describe the implementation of inclusive counseling approaches for deaf children at State Special School (SLB Negeri) Cilacap. This research employed a descriptive qualitative method through observation and in-depth interviews with school counselors. The research subject was a 10-year-old deaf student. The results indicate that the humanistic counseling approach plays a central role in building an empathetic and supportive counseling relationship. Behavioral, cognitive, and Cognitive Behavioral Therapy (CBT) approaches were applied situationally to support adaptive behavior and emotional regulation. The main challenge encountered was limited verbal communication, which requires counselors to master alternative communication strategies such as sign language and visual media. This study concludes that integrative inclusive counseling approaches contribute positively to emotional regulation and social adjustment of deaf children.